THE SUPERSTRING THEORY AND THE SHAPE OF PROTONS AND ELECTRONS - Saleh, Gh; Faraji, M; Alizadeh, R; Dalili, A (MATTER: International Journal of Science and Technology, 2018)
According to “Superstring Theory”, the electron and proton are made of similar tiny supersymmetric strings (Gefter, 2007; Green, Schwarz, & Witten, 2012; Schwarz, 1982; Sharma, 2010). In this paper we introduce a sample particle that is such tiny supersymmetric string or made of it and also we use scientific achievements of experiments about electron and proton specifications to verify and compare the electron and proton dimensions and masses with this sample. By using logical reasons, we reject one of the methods of measuring of electrons’ radius. Finally, using simple mathematical formulas, we prove that although the electrons and protons are both spherical, but one is hollow and the other is dense .